The Filipino woman's grief response to induced abortion - San Diego, Francesca
The purpose of this study is to determine the grief response of the Filipino woman after an induced abortion. It is the author's belief that the psychological impact of abortion on the Filipino woman is significant and longlasting. Research of the literature on the grief phenomenon consistently underlined the different stages experienced by the bereaved. More recent authors, notably Speckard (1987), Reardon (1987), Allison (1990), focused on the grief experienced by women who underwent abortion. Reardon, in particular, identified the Post - Abortion Syndrome (PAS) reported by his subjects. Guidelines for identifying women who may be most susceptible to PAS were also presented. Although a predominantly Catholic country and where abortion is illegal and culturally taboo, the Philippines has its share of abortions. No record of accurate data is available regarding the number of abortions performed. However, Dela Rosa (1988) stated that 155,000 to 750,000 abortions are performed annually. Main reasons for abortion were: economic, too many children and social stigma (in the case of unmarried women). No studies are currently available regarding the emotional effects of abortion on the Filipino woman. In this study, the Filipino woman's grief reaction to induced abortion was explored and 60 Filipino women participated in a 45 minute interview, individually administered in their homes by trained research assistants. The investigator hypothesized that there is a significant degree of grieving over the loss of her child by the Filipino woman who chooses to abort. The results showed a wide range of behaviors and grief reactions manifested by the 60 subjects. These were grouped into the 4 tasks of grief response namely re-experience, denial and isolation, impacted grieving, and acceptance and integration. 25 of the subjects admitted having severe grief reactions after their first abortion, 23 considered it mild, while 12 women said they felt no grief at all.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Grief; Grief therapy; Abortion